The Impact of Phloem Feeding Insects on Leaf Ecophysiology Varies With Leaf Age - Pincebourde, Sylvain; Ngao, Jérôme (Frontiers in Plant Science, 2021)
Herbivore insects have strong impacts on leaf gas exchange when feeding on the plant. Leaf age also drives leaf gas exchanges but the interaction of leaf age and phloem herbivory has been largely underexplored. We investigated the amplitude and direction of herbivore impact on leaf gas exchange across a wide range of leaf age in the apple tree–apple green aphid (Aphis pomi) system. We measured the gas exchange (assimilation and transpiration rates, stomatal conductance and internal CO2 concentration) of leaves infested versus non-infested by the aphid across leaf age. For very young leaves up to 15 days-old, the gas exchange rates of infested leaves were similar to those of non-infested leaves. After few days, photosynthesis, stomatal conductance and transpiration rate increased in infested leaves up to about the age of 30 days, and gradually decreased after that age. By contrast, gas exchanges in non-infested leaves gradually decreased across leaf age such that they were always lower than in infested leaves. Aphids were observed on relatively young leaves up to 25 days and despite the positive effect on leaf photosynthesis and leaf performance, their presence negatively affected the growth rate of apple seedlings. Indeed, aphids decreased leaf dry mass, leaf surface, and leaf carbon content except in old leaves. By contrast, aphids induced an increase in leaf nitrogen content and the deviation relative to non-infested leaves increased with leaf age. Overall, the impacts of aphids at multiple levels of plant performance depend on leaf age. While aphids cause an increase in some leaf traits (gas exchanges and nitrogen content), they also depress others (plant growth rate and carbon content). The balance between those effects, as modulated by leaf age, may be the key for herbivory mitigation in plants.